Effect of Firing Condition and Ingredients on the Swelling Behaviour of Iron Ore Pellets - Sharma T.; Prakash B. (My University, 2025)
In the present investigation an attempt has been made to determine the effect of firing temperature, firing time and ingredients/additives (CaO, MgO, SiO2, Al2O3) on the swelling behaviour of iron ore pellets. For this purpose two Indian iron ore fines from Bailadila and Noamundi deposits and chemically pure iron oxide were used. © 1993, The Iron and Steel Institute of Japan. All rights reserved.